Tobacco: A problem that affects young universities at the national and international levels - Correa-López, Lucy E. (2019)
The World Health Organization defines smoking as a chronic addictive disease widespread worldwide. It represents one of the greatest threats to public health, affecting children, youth and adults. It is estimated, that there are 1.300 million smokers in the world and about 80% of these live in countries where there is a high rate of morbidity and mortality associated with tobacco mainly in adult consumers. In particular, the consumption of tobacco among young university students is evident and worrisome. Different authors in the world have raised factors for tobacco use among adolescents and young adults. Such studies argue that the habit of smoking usually begins during adolescence and consolidates in the university stage. Smoking in parents, relatives, and friends is a factor, perhaps the most remarkable, which is associated with the acquisition of smoking as a habit.